2010
DOI: 10.1080/10862961003796173
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Explicitly Teaching Story Structure to Primary Grade Children

Abstract: The importance of emergent literacy skills as a foundation for proficient reading has led to the development of interventions to teach these skills. These interventions are particularly important for children from disadvantaged homes because they often lack the home literacy experiences necessary for building foundational literacy skills prior to school entry. While previous interventions have been successful in developing literacy skills, noticeably absent has been instruction to develop comprehension. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
1
23
0
4
Order By: Relevance
“…In narrative stories, important elements of a story (i.e., text structure) typically include main characters, the setting, an initiating event, a problem, attempts to solve the problem, and the resolution (Baker and Stein 1981; Fitzgerald 1989). Text structure knowledge appears to help spoken language and reading comprehension because it provides schemas to organize and understand new information (Stevens et al 2010; Williams et al 2009), process meaning construction (Anderson et al 1977; Bransford and Johnson 1972), analyze stories (Trabasso 1981), and support inference generation (Tompkins and McGee 1989; Trabasso and Wiley 2005). …”
Section: Comprehension Monitoring and Providing Awareness Of Story Stmentioning
confidence: 99%
“…In narrative stories, important elements of a story (i.e., text structure) typically include main characters, the setting, an initiating event, a problem, attempts to solve the problem, and the resolution (Baker and Stein 1981; Fitzgerald 1989). Text structure knowledge appears to help spoken language and reading comprehension because it provides schemas to organize and understand new information (Stevens et al 2010; Williams et al 2009), process meaning construction (Anderson et al 1977; Bransford and Johnson 1972), analyze stories (Trabasso 1981), and support inference generation (Tompkins and McGee 1989; Trabasso and Wiley 2005). …”
Section: Comprehension Monitoring and Providing Awareness Of Story Stmentioning
confidence: 99%
“…Key narrative componentscharacters, problem, attempted solutions, and solution -are articulated (Stevens, et al, 2010). His retelling reinforces skills that support the understanding of text, as he identified story elements that connect the entire narrative (Paris & Paris, 2003).…”
Section: Page 12mentioning
confidence: 95%
“…Paris and Paris (2003, p.40) describe "early narrative competence is a fundamental aspect of children's comprehension of experiences before they begin to read, as it helps children map their understanding onto texts". Building an understanding of story schema that aids recall and supports comprehension (Stevens, Van Meter & Warcholak, 2010). www.ccsenet.org/ies International Education Studies Vol.…”
Section: Understanding Narrative Grammarmentioning
confidence: 99%
“…Strickland & Walker, 2004). Explicit instruction in reading strategies, such as understanding story structure or using context clues to identify unknown words, has been shown to increase students' reading abilities and comprehension (Stevens, Van Meter, & Warcholak, 2010), yet a decontextualized emphasis on skills has shown to be ineffective and detrimental (Barone, 2003;Henson & Gilles, 2003;Triplett, 2007). In a large-scale study examining the effects of different instructional approaches on elementary students' comprehension level, Block, Parris, Reed, Whiteley, and Cleveland (2009) found that workbook practice and basal readers produced the lowest levels of reading achievement, whereas a transactional approach in which students read text with discussions guided by teachers had the most positive effects.…”
Section: Review Of the Related Literaturementioning
confidence: 99%